Are genetic modifiers the answer to different responses to hydroxyurea treatment? A pharmacogenetic study in sickle cell anemia Angolan children - Ginete, Catarina (2023)
Sickle cell anemia (SCA) is an inherited disease affecting the hemoglobin that is particularly common in sub-Saharan Africa. Although monogenic, phenotypes are markedly heterogeneous in terms of severity and life span. Hydroxyurea is still the most common treatment for these patients, and the response to treatment is highly variable and seems to be an inherited trait. Therefore, identifying the variants that might predict hydroxyurea response is important for identifying patients who will have a poorer or non-response to treatment, and the ones that are more prone to suffer from severe side effects. In the present pharmacogenetic study, we analyzed the exons of 77 genes described in the literature as potentially associated with hydroxyurea metabolism in Angolan children treated with hydroxyurea and evaluated the drug response considering fetal hemoglobin levels, other hematological and biochemical parameters, hemolysis, number of vaso-occlusive crises and hospitalizations. Thirty variants were identified in 18 of those genes as possibly associated with drug response, five of them in gene DCHS2. Other polymorphisms in this gene were also associated with hematological, biochemical, and clinical parameters. Further research examining the maximum tolerated dose and fixed-dose with a larger sample size is necessary to corroborate these findings.